In memoriam: Carl J. Carrano - Frithjof C. Küpper; Eleanor Carrano; Kenneth N. Raymond; Eric Miller; Ricardo Cruz-López; Ana Mijovilovich; Kyoko Yarimizu; Andrew Cooksy; Wes Harris; Shady A. Amin; Alison Butler; John C. Carrano (BioMetals, 2026)
This article is a celebration of the life and work of Carl J. Carrano who, from a childhood in Long Island, New York, built a career in bioinorganic chemistry, especially in the context of metal uptake and halogen metabolism in microbes and marine organisms.

Acyl peptidic siderophores: structures, biosyntheses and post-assembly modifications - Michelle P. Kem; Alison Butler (BioMetals, 2015)

Identification of new members within suites of amphiphilic marine siderophores - Julia M. Vraspir; Pamela D. Holt; Alison Butler (BioMetals, 2011)

Siderophores of Marinobacter aquaeolei: petrobactin and its sulfonated derivatives - Vanessa V. Homann; Katrina J. Edwards; Eric A. Webb; Alison Butler (BioMetals, 2009)

Marine Siderophores and Microbial Iron Mobilization - Alison Butler (BioMetals, 2005)